Танго над пропастью: роман / Нора Робертс ; [перевод с английского В. Пророковой] - Робертс Нора (ЭКСМО, 2002)
Экземпляры: ф.5 (2003) / Инвентарный номер: 47485 / Цена: / Сис.шифр: 84(7Сое)-44 / Авт.знак: Р 58 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44